Pelanggaran Hukum Humaniter Internasional dalam Agresi Militer Israel ke Gaza Pasca-Serangan Hamas 7 Oktober 2023 - Al Farauqi, Mohamad Dziqie Aulia; Mariana, Mariana (Jurnal ICMES, 2024)
Israel's attack on the Palestinian Gaza Strip drew an international reaction because of the large number of civilian casualties caused by the attack. This article aims to identify violations of International Humanitarian Law committed by Israel in Gaza after 7 October 2023. The research method used is a normative legal research method using a case approach to determine the law's suitability with the facts in the case. The findings of this article are that Israel has committed violations of International Humanitarian Law, including violations against civilians and civilian objects, children, medical personnel, and journalists, the use of dangerous chemical weapons, and blocking the entry of humanitarian aid.